Malassezial Dermatitis In A Guinea Pig – A Case Report - Seemanthini, R.; Tresamol, P.V.; Vinodkumar, K.; Suchithra, S.; Sreenesh , S. (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Malasseziapachy dermatis is a commensal, lipophilic basidiomycetes yeast of ovoid or ellipsoidal shape with a thick wall, without production of pseudo mycellium (David et al., 2003).It is commonly found on the skin of dogs and around 50% of clinically healthy dogs are carriers of this yeast (Patterson and Frank, 2002). Malassezia has been very rarely recovered from rodents or lagomorph species (Vega and Castella, 2011). Alterations of cutaneous microclimate and host defence mechanisms allow organisms to multiply and become pathogenic.The present paper describes a case of malassezial dermatitis in a guinea pig and its successful treatment with topical application of miconazole.